STRATEGI PENGAWALAN SUMBER BUTUNG SEBAGAI OBJEK WISATA DALAM MENGATASI POLUSI AIR DAERAH TEMPEH KABUPATEN LUMAJANG - Yushardi; Putri Wihatma Andianti (UHN IGB Sugriwa Denpasar, 2022)
Sumber Butung is a river located in Tempeh Tengah Village, Lumajang Regency. This river is widely used by local people as a source of water that plays an important role in life. The people who live in Tempeh Tengah Village use Sumber Butung as a place for fishing, bathing, washing clothes, and even doing clean water activities in the river (BABS). One of the activities that are often carried out is bathing and washing clothes, where the soap used for washing is like a detergent made from various chemical compounds such as builders, artificial fragrances, and the most dangerous is surfactants. This can cause various diseases such as skin diseases, and plastic packaging made of soap that is not environmentally friendly can contaminate the soil or water around this source. Bathing and washing clothes trigger the occurrence of soapy water waste in the river which can cause the river water to lack oxygen and endanger the lives of the fish in it. Seeing this condition, we want to take control so that Sumber Butung is not polluted. One of them is to make Sumber Butung a tourist attraction that can help the local community's economy and avoid the occurrence of soapy water waste at Sumber Butung. In addition, the reason for making this place a tourist attraction is the location close to the Petilasan House and the Al Habib Sholeh Well. So that with this control, it is hoped that the rivers will remain clean and can continue to be used for the future and the existing historical and cultural places can be known by the wider community.